1984
DOI: 10.1007/bf02907495
|View full text |Cite
|
Sign up to set email alerts
|

Modification of amino acid residues in the S 1 ′ binding site of carboxypeptidase Y

Abstract: Carboxypeptidase Y was treated under different conditions with various reagents in order to chemically modify amino acid side-chains located in the S~ binding site. Treatment of carboxypeptidase Y with H202 in phosphate buffer caused a reduction in the peptidase activity towards FA-Phe-~Leu-OH to 25 % of the control while the esterase activity towards FA-Phe-~OMe, the amidase activity towards FA-Phe~-NH2 and the peptidyl amino acid amide hydrolase activity towards FA-Phe-~GIy-NH2 were much less affected. The l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1984
1984
1988
1988

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…It has previously been shown that chemical modification of two methionyl residues and a single cysteinyl residue in CPD-Y causes alterations in the enzymatic properties of the enzyme (1,3,6,7) and hence, it may be inferred that these amino acid residues are located in the active site of the enzyme. In the present paper they have been identified as Met-313, Met-398 and Cys-341.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been shown that chemical modification of two methionyl residues and a single cysteinyl residue in CPD-Y causes alterations in the enzymatic properties of the enzyme (1,3,6,7) and hence, it may be inferred that these amino acid residues are located in the active site of the enzyme. In the present paper they have been identified as Met-313, Met-398 and Cys-341.…”
Section: Discussionmentioning
confidence: 99%
“…(9). In addition, the active site contains a cysteinyl and a methionyl residue located at the St and S; binding sites, respectively (1,3,6,7), and an additional methionyl residue is presumably located in an as yet unidentified portion of the active site (7). Chemical modifications of these amino acid residues have produced active derivatives with specificities which deviate from that of CPD-Y and it has been shown that these derivatives with advantage can be used in place of unmodified CPD-Y in certain processes concerning enzymatic peptide synthesis (4,5,6).…”
Section: Introductionmentioning
confidence: 99%
“…KUHN et al (113) have described that alkylation ofa methionyl residue in carboxypeptiase Y with iodoacetamide causes a reduction in the peptidase activity of the enzyme without significantly altering the esterase activity. In this laboratory, this methionyl residue has been identified as Met-398 in the amino acid sequence (36) and in addition it has been alkylated with phenacylbromide, m-nitrophenacylbromide and p-nitrophenacylbromide (34) and oxidized with H202 (35). All these derivatives of carboxypeptidase Y have been separated from residual unmodified enzyme by affinity chromatography and characterized kinetically (34,35).…”
Section: Modification At the S; Binding Sitementioning
confidence: 99%
“…In this laboratory, this methionyl residue has been identified as Met-398 in the amino acid sequence (36) and in addition it has been alkylated with phenacylbromide, m-nitrophenacylbromide and p-nitrophenacylbromide (34) and oxidized with H202 (35). All these derivatives of carboxypeptidase Y have been separated from residual unmodified enzyme by affinity chromatography and characterized kinetically (34,35). Modification of carboxypeptidase Y with phenacylbromide influences KdK~ for the hydrolysis of ester and amide substrates in a manner which is dependent on the size of the leaving group of the substrate (Table VIII).…”
Section: Modification At the S; Binding Sitementioning
confidence: 99%
“…Since the amino acid occupying position 398 is part of the S~ binding site (8,9) Cys-CPD-Y was characterized kineticaUy using a series of FA-ester, FA-peptide and FA-amide substrates with different groups in the P; position. Exchange of Met-398 with a cysteinyl residue resulted in a reduction in k~,dK~ for all the substrates listed in Table I and [I (with the exception of FA-Ala-OBzl) due to decreased k~, values and increased Km values.…”
Section: Peptide Synthesis and Deamidation Of Peptide Amidesmentioning
confidence: 99%